HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) ON RUJAK ULEK TRADERS IN BANDAR KHALIPAH VILLAGE, DELI SERDANG DISTRICT IN 2024 - Ashar, Yulia Khairina; Melisa, Melisa; Dalimunthe, Halimatus Sa'diyah; Lubis, Syahrani; Ar-ramdhani, Adinda Aulia; Sagala, Rahmadani; Yusrina, Tania; Sitompul, Muhammad Rizky Ramadhan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Based on the website of the Centre for Food and Drug Policy Analysis, in Indonesia in 2023 there were 1772 incidents due to food poisoning. North Sumatra Province is the fifth highest case in Indonesia in the scope of the region due to food poisoning. Good implementation should be applied in the HACCP food management quality system. Making rujak ulek from production to the final stage to consumers allows the fruit to be contaminated with pollutants because the fruit contains almost 100% water so it is easily damaged. This study aims to identify hazards related to the process of making rujak ulek in Bandar Khalipah Village, Deli Serdang Regency in 2024. This research is qualitative type with descriptive observational method using HACCP approach. The total sample used was 32 rujak ulek traders specifically on Jalan Pasar 7, Bandar Khalipah Village. This study uses research instruments in the form of interview guidelines, observation forms and stationery. The results showed that most of the rujak ulek traders have not fulfilled Personal Hygiene, Place/Sanitation Facilities, Processing/Serving of Good Food according to the Indonesian Minister of Health No. 942/Menkes/SK/VII/2003. Based on hazard identification there are 2 potential hazards and critical control points there are 4 processes identified in the process of making rujak ulek. There are researcher recommendations for rujak ulek traders related to personal hygiene and place/sanitation infrastructure and it is recommended to develop a HACCP system.